A novel technique for endoscope progression in gastroscopy resection: forward-return way for dissection of stromal tumor in the muscularis propria of the gastric fundus - Guo, Hai-Mei; Sun, Ying; Cai, Shuang; Miao, Feng; Zheng, Yan; Yu, Yang; Zhao, Zhi-Feng; Liu, Lu (Frontiers in Oncology, 2023)
Background: The fundus of the stomach is a challenging region for endoscopic resection of gastrointestinal stromal tumors (GISTs), especially in the anterior wall of the fornix at the side of the greater curvature. This study aimed to introduce the Forward-Return Way (FRW) technique in gastric fundus operations and provide evidence of its advantages. The FRW technique allows the gastroscope to access the stomach fornix without entering the gastric antrum after passing through the gastric cardia. Using FRW, the gastroscope body makes a forward return along the wall of the posterior wall of the upper gastric body and the wall of the greater curvature. Methods: The clinical data of patients with stromal tumors in muscularis propria at the gastric fundus (STMF) at the Fourth Hospital of China Medical University between May 2020- March 2021 were reviewed. The novel FRW technique was used in the procedures, and the beneficial effects, suitability, applicable lesion site, and success rates of FRW were analyzed. Results: A total of 10 cases were reviewed, and the FRW technique was successfully performed in 7 cases (70%). The gastroscope’s tip reached the area just below the gastric cardia, allowing endoscopists to successfully access all angles and sites of the stomach’s fundus in all seven patients. The lesion was easily accessed, and the gastroscope was stable with good left-right and forward-backwards movements. Conclusion: The FRW technique significantly facilitates the resection of the GISTs by aligning the endoscopy body movement direction with the observation direction.